Male-Specific Differences in Proliferation, Neurogenesis, and Sensitivity to Oxidative Stress in Neural Progenitor Cells Derived from a Rat Model of ALS - Li, Ruojia; Strykowski, Rachel; Meyer, Michael; Mulcrone, Patrick; Krakora, Dan; Suzuki, Masatoshi (PLOS ONE, 2012)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease characterized by progressive motor dysfunction and the loss of large motor neurons in the spinal cord and brain stem. A clear genetic link to point mutations in the superoxide dismutase 1 (SOD1) gene has been shown in a small group of familial ALS patients. The exact etiology of ALS is still uncertain, but males have consistently been shown to be at a higher risk for the disease than females. Here we present male-specific effects of the mutant SOD1 transgene on proliferation, neurogenesis, and sensitivity to oxidative stress in rat neural progenitor cells (rNPCs). E14 pups were bred using SOD1G93A transgenic male rats and wild-type female rats. The spinal cord and cortex tissues were collected, genotyped by PCR using primers for the SOD1G93A transgene or the male-specific Sry gene, and cultured as neurospheres. The number of dividing cells was higher in male rNPCs compared to female rNPCs. However, SOD1G93A over-expression significantly reduced cell proliferation in male cells but not female cells. Similarly, male rNPCs produced more neurons compared to female rNPCs, but SOD1G93A over-expression significantly reduced the number of neurons produced in male cells. Finally we asked whether sex and SOD1G93A transgenes affected sensitivity to oxidative stress. There was no sex-based difference in cell viability after treatment with hydrogen peroxide or 3-morpholinosydnonimine, a free radical-generating agent. However, increased cytotoxicity by SOD1G93A over-expression occurred, especially in male rNPCs. These results provide essential information on how the mutant SOD1 gene and sexual dimorphism are involved in ALS disease progression.